The Coevolutionary Relationship of Technology, Market and Government Regulation in Telecommunications - Xuchen Lin; Ting-Jie Lu; Xia Chen (International Telecommunications Society (ITS), 2017)
The technical change in telecommunications industry is tremendous, and it is exactly the continuous technological progress in telecommunications that brings sustained prosperity and development of the telecommunications industry. Inthis paper, the interplay between technology, market and government in telecommunicationsis discussed brieflyin the first place, and thenwe introduce technologyand government into the traditional SCP paradigm as essential factorswhich have economic meaningstoconstruct a new industry analysis framework called TGM (SCP). Basedon this framework, we propose thespiral coevolutionmodel of telecommunications industrywhich elaborates on the interaction mechanism between technological innovation, government regulation and market evolution in telecommunications. Our study indicatesthatthe evolution of the telecommunications industry is the result of technological innovation, government regulation and market competition, and among the three, technological innovation is the fundamental driving force. Compared to the “invisible hand”—market and “visible hand” —government, we believe that technology is the “third hand” in telecommunications industry. The policy implications regarding thesefindingsaregiven at the end of this paper.
Keywords: 330; technological innovation; government regulation; telecommunications; industry analysis